EDUKASI PENGGUNAAN MEDIA SOSIAL BAGI PEMILIH PEMULA SEBAGAI SARANA KAMPANYE PEMILU SERENTAK 2024 DI DESA SUMERTA KELOD - I Made Sudiksa; , I Nyoman Sunarta; Gusi Putu Lestara Permana; Ketut Elly Sutrisni; Kelvin Cahya Utomo (Sewagati, 2024)
In an effort to ensure the success of the 2024 elections and the creation of peaceful democracy, one approach that can be taken is educating first-time voters on the use of social media. The active role and participation of first-time voters are crucial for the progress of the Indonesian nation. In this regard, the role of academics through community service is very important in ensuring the success of the elections. This community service activity is carried out through thematic community service projects. The goal is to enhance the understanding of first-time voters in Sumber Kelod Village, Denpasar City. The educational method is implemented through socialization using brochures. This socialization is very beneficial and provides new insights for first-time voters. The results of this education are significant in shaping a generation of intelligent, critical, and responsible voters. With sufficient knowledge, high political awareness, and an independent attitude, first-time voters can participate actively and effectively in elections, thereby contributing to a better and higher quality democratic process. Continuous education is essential to ensure that each new generation of voters is prepared to face the challenges and responsibilities in their political lives.